Patterns of post-acute health care utilization after a severe traumatic brain injury: Results from the PariS-TBI cohort. (June 2015) - Jourdan, Claire; Bayen, Eleonore; Darnoux, Emmanuelle; Ghout, Idir; Azerad, Sylvie; Ruet, Alexis; Vallat-Azouvi, Claire; Pradat-Diehl, Pascale; Aegerter, Philippe; Weiss, Jean-Jacques; Azouvi, Philippe
Abstract Objective: To assess brain injury services utilization and their determinants using Andersen's model. Methods: Prospective follow-up of the PariS-TBI inception cohort. Out of 504 adults with severe traumatic brain injury (TBI), 245 survived and 147 received a 4-year outcome assessment (mean age 33 years, 80% men). Provision rates of medical, rehabilitation, social and re-entry services and their relations to patients' characteristics were assessed. Results: Following acute care discharge, 78% of patients received physiotherapy, 61% speech/cognitive therapy, 50% occupational therapy, 41% psychological assistance, 63% specialized medical follow-up, 21% community re-entry assistance. Health-related need factors, in terms of TBI severity, were the main predictors of services. Provision of each therapy was significantly associated with corresponding speech, motor and psychological impairments. However, care provision did not depend on cognitive impairments and cognitive therapy was related to pre-disposing and geographical factors. Community re-entry assistance was provided to younger and more independent patients. Conclusions: These quantitative findings illustrate strengths and weaknesses of late brain injury care provision in urban France and highlight the need to improve treatment of cognitive impairments.